A novel object recognition method based on improved edge tracing for binary images - Talu, M.F.; Türko?lu, I. (My University, 2009)
In this article, we mention about a novel object recognition method based on an improved edge tracing method for binary images. This method named as "NORMBI" (novel object recognition method in binary images) contains two subsequent processes, determining places of independent objects (the starting point detection algorithm) and obtaining their edge points and geometrical shapes information (the edge tracing algorithm). The most important difference between NORMBI and traditional methods is to obtain geometrical shapes information and edge points of objects simultaneously by scanning image matrix once. It means to improve speed factor that has a vital important for object recognition. Besides, a tool has been designed to obtain the performance differences in between NORMBI and traditional methods. The mathematical results obtained are represented comparatively in a tabular format. ©2009 IEEE.
2009 International Conference on Application of Information and Communication Technologies, AICT 2009 -- 14 October 2009 through 16 October 2009 -- Baku -- 79447
Keywords: Binary image; Edge tracing; Object recognition